The Implementation of Interactive Learning Strategies to Enhance Maharah Kalam among Arabic Language Students at STAI Ali bin Abi Thalib Surabaya - Muhammad Dimas Prasetyo; Zaki Ulien Nuha; Umar Husnan (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2025)
This study aims to describe the implementation of interactive learning strategies, identify supporting and inhibiting factors, and analyze their contribution to improving Arabic speaking skills (maharah kalām) among Arabic Language students at STAI Ali bin Abi Thalib Surabaya. The study is motivated by the persistence of teacher-centered practices that limit students’ opportunities to actively practice speaking Arabic. A descriptive qualitative approach was employed, involving two lecturers of hiwar courses and Arabic Language students as research participants. Data were collected through classroom observations, in-depth interviews, and documentation, and analyzed using the Miles and Huberman model. The findings indicate that interactive learning strategies were implemented through contextual vocabulary introduction, practice of dialogues, role plays, conversational simulations, and dialog-based exercises that actively involved all students. Lecturers played a central role as facilitators by creating a communicative classroom atmosphere, providing motivation, and correcting students’ speaking practices. Supporting factors included textbooks, repeated dialogue practice, varied learning activities, and lecturers’ personal approaches, while inhibiting factors consisted of differences in students’ initial language abilities, limited vocabulary mastery, and psychological barriers such as lack of confidence. Overall, interactive learning strategies contributed positively to enhancing students’ speaking confidence, vocabulary acquisition, and ability to construct contextual Arabic sentences within Islamic higher education.